Prognóstico da toxidez de ferro em arroz irrigado por alagamento através da análise de solo pelo método oxalato de amônio - Wolter, Roberto Carlos Doring (2010)
Iron toxicity can cause considerable reductions in the productivity of rice, depending on the severity of symptoms and the affected area in the field. It is necessary to identify the factors that determine the occurrence of this nutritional disorder, so that effective measures may be carried out to correct this problem in the field. The objective of this study is to verify that the interpretation criteria for prognosis of the risk of iron toxicity in flooded rice using the soil analysis are reliable for a particular group of lowland soils. Thus, an experiment was conducted in the greenhouse, and the treatments made up of eleven lowland soils structured with a one-factor randomized block design, with four replications. The indicators were: iron extracted from the soil and the CEC, to estimate the percentage of saturation of CEC by Fe2+, percentage of symptoms of iron toxicity, weight of dry matter, and calcium, magnesium, iron and manganese contents in the soil solution and plant tissue. The results were subjected to analysis of variance (Duncan test) at 5% probability, and simple linear correlation of Pearson analyzes (whereas levels greater than 95%). The indicators which have the best efficiency to predict the risk of toxicity by iron is the iron concentrationt in the soil solution and PSFe2+. The PSFe2+ has a high correlation coefficient with the concentration of iron in the soil solution. No symptoms of toxicity by iron is observed when the mole ratio of iron by divalent cations in soil solution is less than 0.30. The extraction of iron by ammonium oxalate at pH 6.0 is a good indicator for estimating the iron that is accumulated during the flooding. The interpretation for prediction of the risk of occurrence of iron toxicity in rice proposed by SOSBAI (2007) based on PSFe2+ is efficient for predicting the occurrence of the problem for the group of soils in the study.